Targeting lipid reprogramming in the tumor microenvironment by traditional Chinese medicines as a potential cancer treatment - Qian Zuo; Yingchao Wu; Yuyu Hu; Cui Shao; Yuqi Liang; Liushan Chen; Qianqian Guo; Ping Huang; Qianjun Chen (Heliyon, 2024)
In the last ten years, there has been a notable rise in the study of metabolic abnormalities in cancer cells. However, compared to glucose or glutamine metabolism, less attention has been paid to the importance of lipid metabolism in tumorigenesis. Recent developments in lipidomics technologies have allowed for detailed analysis of lipid profiles within cancer cells and other cellular players present within the tumor microenvironment (TME). Traditional Chinese medicine (TCM) and its bioactive components have a long history of use in cancer treatments and are also being studied for their potential role in regulating metabolic reprogramming within TME. This review focuses on four core abnormalities altered by lipid reprogramming in cancer cells: de novo synthesis and exogenous uptake of fatty acids (FAs), upregulated fatty acid oxidation (FAO), cholesterol accumulation, which offer benefits for tumor growth and metastasis. The review also discusses how altered lipid metabolism impacts infiltrating immune cell function and phenotype as these interactions between cancer-stromal become more pronounced during tumor progression. Finally, recent literature is highlighted regarding how cancer cells can be metabolically reprogrammed by specific Chinese herbal components with potential therapeutic benefits related to lipid metabolic and signaling pathways.